PENGARUH PERPUTARAN KAS, PERPUTARAN PIUTANG, LIKUIDITAS DAN SOLVABILITAS TERHADAP PROFITABILITAS PADA PERUSAHAAN SUB SEKTOR PERBANKAN YANG TERDAFTAR DI BEI PERIODE 2014-2018 - ZAKIA FADILA (LP2MTBM MAKARIOZ, 2019)
Profitability depends on the level of cash turnover, accounts receivable turnover, liquidity and solvency of the company in acertain period. The purpose of this study is to examine the effect of the level of cash turnover, accounts receivable turnover,liquidity and solvency on profitability in banking sub-companies listed on the Indonesia Stock Exchange in the period 2014-2018. This type of research is quantitative research, with a research population of 51 conventional and Islamic banking subsectorslisted on the Indonesia Stock Exchange.The research sample of 28 companies. The results showed that cash turnover, accounts receivable turnover, liquidity andsolvency had a significant effect on profitability in BEI listed banking sector companies in the 2014-2018 period with anadjusted R square value of determination coefficient of 0.109 or equal to 10.9% and the remaining 81.9% influenced by othervariables not included in this study.